1992
DOI: 10.1136/bjsm.26.1.54
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine in exercise adaptation.

Abstract: By influencing the regulation of the mechanisms of angiogenesis, erythropoietin production, blood flow, myocardial glucose uptake, glycogenolysis, systolic blood pressure, respiration, plasma norepinephrine and epinephrine levels, adenosine may exert a significant effect on the body's adaptation response to exercise. However, adenosine's possible influence over the vasodilatory response to exercise in skeletal muscle is controversial and more research is required to resolve this issue. Various popular exercise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 61 publications
0
12
0
1
Order By: Relevance
“…One possible mechanism for elevated AOE activities in the trained animals could be that the mitochondria consumes more oxygen to provide ATP through oxidative phosphorylation. Adenosine, a product of ATP, is reported to have several regulative effects on the body's complex adaptation to exercise, one of which may be an induction of AOE activity (Simpson and Phillis, 1992). Furthermore, the fact that elevated activity was seen in the SW-T(N) rats prompts us to speculate that an AO supplementation may not be a pre-requisite in the young, unlike in the old, where an AO-enriched diet is essential.…”
Section: Discussionmentioning
confidence: 95%
“…One possible mechanism for elevated AOE activities in the trained animals could be that the mitochondria consumes more oxygen to provide ATP through oxidative phosphorylation. Adenosine, a product of ATP, is reported to have several regulative effects on the body's complex adaptation to exercise, one of which may be an induction of AOE activity (Simpson and Phillis, 1992). Furthermore, the fact that elevated activity was seen in the SW-T(N) rats prompts us to speculate that an AO supplementation may not be a pre-requisite in the young, unlike in the old, where an AO-enriched diet is essential.…”
Section: Discussionmentioning
confidence: 95%
“…Roque, et al [25] showed enhanced extracellular adenine nucleotides hydrolysis, increased activity and expression of heart 5'-nucleotidase, and increased coronary blood flow and angiogenesis. This suggests that Ado exerts a strong effect on the adaptation to exercise by affecting the angiogenesis regulation, erythropoietin production, plasma norepinephrine, and epinephrine levels, myocardial glucose uptake, and alternating blood flow, glycogenolysis, systolic blood pressure, and respiration [26][27][28].…”
Section: Plasma Purine Derivativesmentioning
confidence: 99%
“…Since adenosine production is dependent on the amount of adenosine triphosphate (ATP) catalysis, the level of adenosine increases under stress conditions, such as endurance training or increased use of ATP over time. It seems that adenosine plays an important role in the complex adaptation of the body to endurance training; because of its rapid production, it is considered an ideal molecular agent for many regulatory mechanisms (44).…”
Section: Discussionmentioning
confidence: 99%